Best practices in customs administrations: a preliminary exploratory study - Morini, Cristiano (Revista de Administração da UFSM, 2015)
This work focuses on the competitiveness seen by the customs procedures involved. Customs can be considered as a bottleneck in international logistics in some countries. Through an exploratory and bibliographical research, we could understand the main characteristics of the customs procedures in Brazil compared with the characteristics of countries considered as world reference. The analysis was based on information drawn from websites of the customs administrations of the countries that initiated the implementation of internationally accepted "good practices’, according to criteria of the World Bank and other international organizations. It is crucial to note the best practices and benchmarking in the customs environment. Among the best practices observed, we highlight the electronic transmission of data, the analysis of risk based on prior information, cooperation at various levels, the use of information technology in transmission and registration procedures, compliance with the Revised Kyoto Convention, among others. Brazil has some actions targeted at best practices, but we need greater agility and coordination in the implementation of most of them.